Bacterial RTX toxins and host immunity. Issue 3 (June 2021) - Ahmad, Jawid Nazir; Sebo, Peter
Abstract : Purpose of review: RTX toxin action often defines the outcome of bacterial infections. Here, we discuss the progress in understanding the impacts of RTX toxin activities on host immunity. Recent findings: Bordetella pertussis CyaA activity paralyzes sentinel phagocytic cells by elevating cellular cAMP levels and blocks differentiation of infiltrating monocytes into bactericidal macrophages, promoting also de-differentiation of resident alveolar macrophages into monocyte-like cells. Vibrio cholerae multifunctional autoprocessing repeats-in-toxins (MARTX), through Rho inactivating and α/β-hydrolase (ABH) domain action blocks mitogen-activated protein kinase signaling in epithelial cells and dampens the inflammatory responses of intestinal epithelia by blocking immune cell recruitment. The action of actin crosslinking effector domain and Ras/Rap1-specific endopeptidase (RRSP) domains of MARTX compromises the phagocytic ability of macrophages. Aggregatibacter actinomycetemcomitans LtxA action triggers neutrophil elastase release into periodontal tissue, compromising the epithelial barrier and promoting bacterial spreads into deeper tissue. Summary: Action of RTX toxins enables bacterial pathogens to cope with the fierce host immune defenses. RTX toxins often block phagocytosis and bactericidal reactive oxygen species and NO production. Some RTX toxins can reprogram the macrophages to less bactericidal cell types. Autophagy is hijacked for example by the activity of the V. cholerae ABH effector domain of the MARTX protein. Subversion of immune functions by RTX toxins thus promotes bacterial survival and proliferation in the host.